Grouting technique—combining transvenous Onyx and coils for the embolization of complex non-cavernous intracranial dural arteriovenous fistulas - Chen, Ching-Chang; Chen, Chun-Ting; Wu, Yi-Ming; Yeap, Mun-Chun; Chen, Yao-Liang; Wong, Ho-Fai (Frontiers in Neurology, 2024)
Objective Incomplete occlusion of cerebral dural arteriovenous fistula (DAVF) may lead to fistula recurrence and rebleeding, which may necessitate several embolizations and lead to worse clinical outcomes. Herein, we describe a grouting technique for endovascular embolization and its outcomes in a series of patients with complex intracranial DAVF. Methods A total of 20 patients with aggressive type or symptomatic intracranial non-cavernous DAVF underwent endovascular transvenous embolization combining detachable coils and Onyx. Two microcatheters were positioned either in the distal segment of the involved sinus or near the draining veins. To achieve tight occlusion of the involved sinus, coils were carefully delivered through the first microcatheter, starting from the distal segment and then to the proximal segment. Next, Onyx was injected through the second microcatheter to reinforce and fill (grout) the interspace of coil mass and gradually refluxed to the mural channels and para-sinus cortical veins until the fistula was completely occluded. Results Successful embolization was achieved in all 20 patients. The initial angiographic results revealed the achievement of complete occlusion in 19 patients (95%). At the postembolization follow-up, complete obliteration of the fistula was achieved in all patients (100%). No symptom or angiographic recurrence was observed at the 2- to 5-year follow-ups. No patient required additional embolization or stereotactic radiosurgery. Conclusion The proposed grouting technique combining detachable coils and Onyx appears to be promising for the elimination of complex intracranial non-cavernous DAVFs.